ANALYSIS OF SOCIODEMOGRAPHIC FACTORS AND EXCLUSIVE BREASTFEEDING SUCCESS IN KARANGANYAR DISTRICT - Wigunantiningsih, Ana; SUkoco, Amin (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
Breastfeeding is a crucial program with a significant impact on the health and nutrition of toddlers. Additionally, it also offers benefits for mothers. In 2018, the rate of exclusive breastfeeding in Central Java Province was 65.57%, while Karanganyar District stood at 62.3%. Various factors influence exclusive breastfeeding, including interpersonal relationships, mother and baby characteristics, environmental factors, support systems, institutional elements, and socioeconomic and cultural conditions. This study aimed to assess sociodemographic factors' influence on exclusive breastfeeding's success. It employed an analytic, cross-sectional approach and utilized purposive sampling, involving 55 mothers with infants aged 0-6 months who visited the Health Center for child immunization. The research instrument used was a closed questionnaire, and data analysis was conducted using logistic regression analysis with the SPSS version 16.0 program. The findings revealed that three of five sociodemographic variables—parity, education level, and maternal employment status—significantly affected exclusive breastfeeding. Sociodemographic factors influence exclusive breastfeeding success by 52.1%, indicating that 48.9% of other factors beyond the variables studied also play a role. These research results can inform the development of health education programs for pregnant women in their third trimester, focusing on exclusive breastfeeding in preparation for the breastfeeding period.